EVALUASI KEGIATAN UKS DI SEKOLAH DASAR X DALAM PENERAPAN PROGRAM SEKOLAH SEHAT TAHUN 2022 - Frisca Ajeng Agustina (2023)
In 2022 the government campaigned for Healthy Schools with the theme Revitalizing School Health Enterprises (SHU) with one of the targets being Elementary Schools (ES) which are based on concerns related to the health problems of Indonesian children. Therefore, the study aims to evaluate SHU activities in School X. This study used qualitative methods through observing the form of check and in-depth interview of activities related to the purpose of Healthy School, namely Health Screening and Periodic Health Checks, Nutrition Education, Physical Activity, and Immunizations. Research indicates that the implementation of the SHU in the 2022 application of Healthy School programs at School X is entirely well performed but there is still discrepancy with the SHU Implementation Module in Elementary School Education Units and the Implementation of the SHU Three Aspects in Limited Face-to-Face Learning during the Pandemic Period. Yet the update of the medical guidelines and the limitations of the means led to inadequate execution of some activities. The recommendation for School X is to renew the SHU guidelines to improve optimal performance of activities in the implementation of a healthy school.